2020
DOI: 10.1186/s13256-020-02410-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ri-associated paraneoplastic ophthalmoplegia-ataxia syndrome in a woman with breast cancer: a case report and review of the literature

Abstract: Background: Breast cancer is the most common cancer in women. However, in the management of breast cancer, paraneoplastic neurological syndromes represent a diagnostic and therapeutic challenge. The diagnosis of paraneoplastic neurological syndromes is difficult due to the heterogeneity of symptoms, the timing of presentation, and the absence of antibodies, and it generally occurs before the diagnosis of breast cancer in 80% of patients who develop paraneoplastic neurological syndromes. We describe a 72-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Our patient presented with a static-kinetic cerebellar syndrome, multiple cranial nerve palsy, and cervical dystonia. In this way, our results confirm the data found in the literature, the opsoclonusmyoclonus syndrome is not pathognomonic of anti-Ri antineuronal antibody [4].…”
Section: Discussionsupporting
confidence: 92%
“…Our patient presented with a static-kinetic cerebellar syndrome, multiple cranial nerve palsy, and cervical dystonia. In this way, our results confirm the data found in the literature, the opsoclonusmyoclonus syndrome is not pathognomonic of anti-Ri antineuronal antibody [4].…”
Section: Discussionsupporting
confidence: 92%
“…However, it has now been demonstrated that malignant tumours may produce antibodies targeted against neural cells (onconeural antibodies) [10,11], highlighting the immune-mediated mechanisms of these disorders. Such antibodies are detected in 70-80% of PNS cases [12]; therefore, their presence is not compulsory for the diagnosis of a paraneoplastic syndrome, while PNS may be diagnosed in the absence of a known primary cancer [13]. In more detail, PNS are subclassi ed in classical, when their association with malignant disease is well established, and non-classical [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the autoimmune nature of these disorders has now been demonstrated: they are mediated by antibodies targeted against tumour-produced antigens that are normally expressed by native neural cells (onconeural antibodies) [ 10 , 11 ]. Such antibodies are detected in 70–80% of PNS cases [ 12 ]; therefore, their presence is not compulsory for the diagnosis of a paraneoplastic syndrome, while PNS may be diagnosed in the absence of a known primary cancer [ 13 ]. In more detail, PNS are subclassified in classical, when their association with malignant disease is well established, and non-classical [ 13 ].…”
Section: Discussionmentioning
confidence: 99%